2014
DOI: 10.1016/j.jad.2014.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety in first-episode psychosis: The role of childhood trauma and adult attachment

Abstract: Michail, Maria and Birchwood, Max (2014) Social anxiety in first-episode psychosis: the role of childhood trauma and adult attachment. Journal of Affective Disorders, 163 . pp. 102-109. ISSN 1573-2517 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/35476/1/Accepted%20manuscript.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 53 publications
1
22
1
2
Order By: Relevance
“…Six studies compared attachment across groups defined by clinical 'caseness' for social anxiety. In five of these, people meeting diagnostic criteria for social anxiety were significantly more likely to be insecurely attached in comparison with healthy control groups (OR = 18.5; d = 0.49 -1.38; Eng et al 2001;Lionberg, 2003;Weisman et al, 2011;Michail & Birchwood, 2014). However, Kashdan and Roberts (2011) observed no difference in attachment to therapeutic group and therapist between depressed service-users with or without social anxiety.…”
Section: Between Group Differencesmentioning
confidence: 91%
See 1 more Smart Citation
“…Six studies compared attachment across groups defined by clinical 'caseness' for social anxiety. In five of these, people meeting diagnostic criteria for social anxiety were significantly more likely to be insecurely attached in comparison with healthy control groups (OR = 18.5; d = 0.49 -1.38; Eng et al 2001;Lionberg, 2003;Weisman et al, 2011;Michail & Birchwood, 2014). However, Kashdan and Roberts (2011) observed no difference in attachment to therapeutic group and therapist between depressed service-users with or without social anxiety.…”
Section: Between Group Differencesmentioning
confidence: 91%
“…In particular, people with social anxiety reported higher attachment anxiety (d = 1.15 -1.45), lower comfort in closeness with attachment figures (d = 1.15 -1.44) and lower ability to trust and depend on attachment figures than healthy controls (d = 0.45 -1.02). A large effect size (OR = 18.5) was found in a small sample of individuals at ultra-high risk for psychosis (Michail & Birchwood, 2014). This estimate was based on a low cell count and so lacks precision and may not be reliable.…”
Section: Between Group Differencesmentioning
confidence: 94%
“…For example, an epidemiological study [28] showed childhood relationship traumas of loss of a parent and adverse parenting practices predicted a variety of anxiety, mood, and substance-use disorders in adulthood, and these effects were greater when the loss was at a younger than older childhood age. Another study [29] found that a history of childhood trauma and particularly emotional and sexual abuse was higher for those adults with social anxiety compared to psychiatric and healthy controls. Kaehler and Freyd [16] examined physical abuse history and found that this kind of significant relationship betrayal predicted BPD features in women, and mothers with diagnosed BPD were more likely to have preoccupied/unresolved attachment status but not more likely to be dismissive [30].…”
Section: Attachment Relationship Trauma and Abusementioning
confidence: 96%
“…It is expressed in terms of non-specific affective manifestations, but often only indirectly assessed through measures of depression and/or anxiety symptomatology. These symptoms constitute a highly prevalent comorbidity in non-affective psychosis, associated with poorer prognosis (Hartley et al, 2013;Lako et al, 2012;Michail and Birchwood, 2014). However, the distress, though highly correlated with anxiety and depression, is a distinct affective feature, being more comprehensive and transient (Ritsner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%